KISHI MEKTEP JASINDAǴI OQIWSHILARDIŃ ANA TILI SABAQLARINDA KLASTAN TIS JUMISLARDI SHÓLKEMLESTIRIW - Saburova, S. (SCIENCE and SOCIETY, 2022)
The article discusses the organization of extracurricular activities at the mother tongue classes of primary school children. Suggestions are made for the widespread use of number of activities at mother tongue lessons at the primary school, such as extracurricular subjects, extracurricular activities, rework of text work, making a plan.